# Matematicas

Solo disponible en BuenasTareas
• Páginas : 14 (3401 palabras )
• Descarga(s) : 0
• Publicado : 19 de marzo de 2011

Vista previa del texto
EJERCICIOS Y PROBLEMAS
1)
2) X + (x+1) = 39
2x + 1 = 39
2x = 38
X = 19

3) X + (x+2) = 54
2x + 2 = 54
2x = 52
X = 26

4) 3x = 20 – x
4x = 20
X = 5

5) 5x – 15 = 3x + 5
(5x – 3x)= 5 + 15
2x = 20
X = 10

6) 8x + 3 = 6x + 4
8x – 6x = 4 - 3
2x = 4 – 3
X = ½7) 4 – (3x – 2) = 12
4 – 3x + 2 = 12
6 – 3x = 12
3x = 6
X = -2

8) 2x/ 3 + x/5 = 26
10x + 3x / 15 = 26
13x = 26 (15)
X = 390/ 13
X = 30

9) X – 81 =3x4-2 ( x+1)5
X – 81 = 15x-8 ( x+1)20
20x – (81) (20) = 15x – 8x – 8
20x – 7x = (81) (20) – 8
13x =1620 – 8
13x = 1612
X = 124

10) x+32- x-14=x+63
2x+6-x+14 = x+63
3x + 21 = 4x + 24
21 – 24 = 4x – 3x
-3 = x

11) 2x-17+ 3x-62= 7-4x4
4x-2+21x-4214= 7-4x4
( 25x – 44) 4 = 14 (7 – 4x)100x – 176 = 98 – 56x
156x = 98 + 176
X = 274/ 156
X = 137/ 78
11 5x-67- 6x-22=3x-1
10x-12-42x+1414=3x-1
2 - 32x = 42x – 14
16 = 74x
16/74= x

12) 6 x-75- 2 x+1= 3x
6x – 42 -10x – 10 = 15x
-4x – 52 = 15x
- 52 = 19x
-52/19 = x
13) 3x-4 2+ 5x-13=2x-12
9x-12+10x-26=2x-12
(19x – 14) 2 = 12x -6
38x – 28 = 12x – 6
26x = 22
X =22/26
X = 11/ 13

14) x-113+ 2x+3169=3
13x-13+2x+3169=3
15x – 10 = 507
15x = 517
X = 517/ 15

15) x-1 4+ x-62 +3 (x-7)12 = 0
3x-3+5x-36+3x-2112=0
12x – 60 = 0
X = 60/12
X = 5

16) 3x-6 18- 1= 2x-54
(3x-6-18)18=2x-54
(3x – 24) 4 = 18 ( 2x – 5)
12x – 96 = 36x– 90
-96 + 90 = 36x -12x
-6 = 24x
-6/24 = x
x = -1/4

17) x+3-x47+ 2x 2-3x53=1
4x+3-x47 + 10x+2-3x53=1
3x+328+7x-215=1
45x+45+196x+55420=1
241 x + 101 = 420
X = 319/ 241
18) 3x- 5x-726+ 3 (x-1)2=0
6x-5x+7 12+ 3 (x-1)2=0
X + 7+ 18x – 18 = 0
19x = 11
X = 11/19
19)3x-12- 3x+1= x 9x+5
9x2- 6x+1-3x-1=9x2+ 5x
-9x = 5x
0 = 14x
X = 0

20) 4x-1 5+13 10+ x-2 2x-7 = 8x-3 10
8x-2 2x-7+ 13 2x-7+ 10x-20 10 (2x-7)= 8x-3 10
15x2-56x-4x+14+26x-91+10x-20 ( 2x-7)=8x-3
16x2 - 24x – 97 = 8x – 3
16x2 - 32x-94=0

21) 5x x-1x2-3x-4 =3 x-1x+1+2(x+1)x-4
5x (x-1)x-4(x+1)=3 (x-1)x+1+ 2 (x+1)x-4
5x (x-1)x-4(x+1)= 3 x-1x-4+ 2 x+1(x+1)x+1(x-4)
5x (x-1) = 3 (x-1) (x-4) + 2 (x +1) (x + 1)
5x2 - 5x= 3x-3x-4+ (2x+2)(x+1)
5x2 - 5x= 3x2 - 12x-3x+12+2x2 + 2x+2x+2
5x2 - 5x=5x2 - 11x+14
6x = 14
X = 14/6
22) x-2x-3+x+2x+1=x+3x+2+x-3x+4
x-2x+1+ x+2x-3x-3x+1=x+3x-4+ x-3(x+2)x+2(x-4)
2x2+x-2x-2+x2-3x+12x-6x2+ x-3x-3 =x2- 4x+3x-12+x2+ 2x-3x-6x2-4x+2x-8
x2- 2x-8x2- 2x-3=x2- 2x-18x2- 2x-8
x2- x-4x-3(x+1)= x2- x-9x-2(x+4)

23) xx-4 + x – 12 = 2 xx+4
x2- 4 x + x – 12 = 4 x + 8x
x- 4x + x – 4x – 8x = 12
2x – 16 x = 12
14 x = 12
X = 1214

24)xx-1/2 + xx+1/2 = 2
x2-1/2 x + x2 +1/2 x = 2
x-1/2 x + x +1/2 x = 2
2x = 2
X =...